Causal relationship between obesity and serum testosterone status in men: A bi-directional mendelian randomization analysis - Eriksson, Joel; Haring, Robin; Grarup, Niels; Vandenput, Liesbeth; Wallaschofski, Henri; Lorentzen, Erik; Hansen, Torben; Mellström, Dan; Pedersen, Oluf; Nauck, Matthias; Lorentzon, Mattias; Nystrup Husemoen, Lise Lotte; et al. (PloS one, 2017)
Obesity in men is associated with low serum testosterone and both are associated with several diseases and increased mortality. Examine the direction and causality of the relationship between body mass index (BMI) and serum testosterone. Bi-directional Mendelian randomization (MR) analysis on prospective cohorts. Five cohorts from Denmark, Germany and Sweden (Inter99, SHIP, SHIP Trend, GOOD and MrOS Sweden). 7446 Caucasian men, genotyped for 97 BMI-associated SNPs and three testosterone-associated SNPs. BMI and serum testosterone adjusted for age, smoking, time of blood sampling and site. 1 SD genetically instrumented increase in BMI was associated with a 0.25 SD decrease in serum testosterone (IV ratio: -0.25, 95% CI: -0.42--0.09, p = 2.8*10-3). For a body weight reduction altering the BMI from 30 to 25 kg/m2, the effect would equal a 13% increase in serum testosterone. No association was seen for genetically instrumented testosterone with BMI, a finding that was confirmed using large-scale data from the GIANT consortium (n = 104349). Our results suggest that there is a causal effect of BMI on serum testosterone in men. Population level interventions to reduce BMI are expected to increase serum testosterone in men.